Antibacterial and Cytotoxicity of Root Canal Sealer with the Addition of Chitosan Nanoparticle at Various Concentrations - Ratih, Diatri Nari; Mulyawati, Ema; Santi, Rika Kurnia; Kristanti, Yulita (European Journal of Dentistry, 2022)
Objectives The aim of this study was to evaluate the addition of chitosan nanoparticle with concentrations of 0, 10, 20, and 30% to the epoxy resin-based (ERB) sealer on its antibacterial and cytotoxicity effect.Methods and Materials This research was divided into two studies, the first study was the addition of chitosan with a concentration of 0% (as control), 10, 20, and 30% to an ERB sealer on its antibacterial effect, and the second study was on its cytotoxicity. An agar diffusion test was employed to determine the antibacterial effect on Enterococcus faecalis. An MTT (3-{4,5-dimethylthiazol-2-yl}-2,5-diphenyl tetrazolium bromide) assay was utilized to test the cytotoxicity by evaluating cell viability.Statistical Analysis One-way analysis of variance and Tukey's test (α = 0.05) were used to analyze data obtained from each evaluation with a significance level of 95%.Results The addition of chitosan nanoparticles at concentrations 10, 20, and 30% produced a greater inhibition zone of E. faecalis (p < 0.05), however, had less cytotoxicity compared with no addition of chitosan (0%) (p < 0.05).Conclusion The addition of chitosan nanoparticles at concentrations 10, 20, and 30% to the ERB sealer produced greater antibacterial and less cytotoxicity compared with no addition of chitosan (0%).
Keywords: antibacterial; chitosan nanoparticle; cytotoxicity; root canal sealer